Recent advances of anti-angiogenic inhibitors targeting VEGF/VEGFR axis - Wang, Lei; Liu, Wang-Qing; Broussy, Sylvain; Han, Bingnan; Fang, Hongming (Frontiers in Pharmacology, 2024)
Vascular endothelial growth factors (VEGF), Vascular endothelial growth factor receptors (VEGFR) and their downstream signaling pathways are promising targets in anti-angiogenic therapy. They constitute a crucial system to regulate physiological and pathological angiogenesis. In the last 20 years, many anti-angiogenic drugs have been developed based on VEGF/VEGFR system to treat diverse cancers and retinopathies, and new drugs with improved properties continue to emerge at a fast rate. They consist of different molecular structures and characteristics, which enable them to inhibit the interaction of VEGF/VEGFR, to inhibit the activity of VEGFR tyrosine kinase (TK), or to inhibit VEGFR downstream signaling. In this paper, we reviewed the development of marketed anti-angiogenic drugs involved in the VEGF/VEGFR axis, as well as some important drug candidates in clinical trials. We discuss their mode of action, their clinical benefits, and the current challenges that will need to be addressed by the next-generation of anti-angiogenic drugs. We focus on the molecular structures and characteristics of each drug, including those approved only in China.